2023
DOI: 10.1002/jcla.24943
|View full text |Cite
|
Sign up to set email alerts
|

The impact and role of identified long noncoding RNAs in nonalcoholic fatty liver disease: A narrative review

Abstract: BackgroundNonalcoholic fatty liver disease (NAFLD) is the most common liver disease worldwide, but its mechanism and pathophysiology remain unclear. Long noncoding RNAs (lncRNAs) may exert a vital influence on regulating various biological functions in NAFLD.MethodsThe databases such as Google Scholar, PubMed, and Medline were searched using the following keywords: nonalcoholic fatty liver disease, nonalcoholic fatty liver disease, NAFLD, nonalcoholic steatohepatitis, nonalcoholic steatohepatitis, NASH, long n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…The expression of LncARSR correlates with the activated state of PI3K/AKT/ mTOR pathway [99] miR-155 Upregulated These ncRNASs have an influence on the induction of inflammation via NF-κB pathway [100,101] Platr4 Upregulated [102] LncTNF Upregulated [103] miR-125 Upregulated…”
Section: Non-coding Rna Expression Primary Function Referencementioning
confidence: 99%
See 2 more Smart Citations
“…The expression of LncARSR correlates with the activated state of PI3K/AKT/ mTOR pathway [99] miR-155 Upregulated These ncRNASs have an influence on the induction of inflammation via NF-κB pathway [100,101] Platr4 Upregulated [102] LncTNF Upregulated [103] miR-125 Upregulated…”
Section: Non-coding Rna Expression Primary Function Referencementioning
confidence: 99%
“…Another lncRNA that has been associated with the pathogenesis and progression of NAFLD to NASH is lncTNF. lncTNF is an intergenic lncRNA that plays a role in liver inflammation, demonstrating a robust response when subjected to TNF-α stimulation [103]. Several studies have shown an upregulation of lncTNF in NAFLD, and the main function associated with it is to promote inflammation via the NF-κB pathway [103].…”
Section: Ncrna Inflammation and Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that several lncRNAs are dysregulated in MASLD patients (for an overview, see [ 54 , 55 ]), and studies report that lncRNAs are involved in lipogenesis and fatty acid metabolism (for an overview, see [ 56 ]). Indeed, Blnc1 function is not restricted to the adipose tissue, as it has been shown to regulate lipogenesis in the liver as well [ 57 ].…”
Section: Lncrnas and Diet-induced Hepatic Steatosismentioning
confidence: 99%
“…Insulin resistance is often a common characteristic of obesity and diet-induced metabolic diseases, such as T2D or MASLD [ 77 ]. While a dysregulated lncRNA profile seems to be involved in the pathogenesis of diet-induced metabolic diseases such as MASLD [ 54 , 55 ], recent evidence suggests that lncRNAs also contribute to the regulation of insulin signaling and glucose metabolism in several tissues and to the pathogenesis of insulin resistance (reviewed in detail by others [ 78 , 79 ]). By controlling pathways of glucose metabolism, the liver has a major role in the control of glucose homeostasis [ 80 ], and insulin resistance seems to be associated with an increase in hepatic glucose output, lipogenesis, and VLDL secretion, leading to a combination of hyperglycemia and hypertriglyceridemia [ 81 ].…”
Section: Lncrna and Glucose Metabolismmentioning
confidence: 99%